Emotional Regulation Mechanisms of University Students in Group Work Situations - Lilyan Vega-Ramírez; Alda Reyno-Freundt; Christian Hederich-Martínez; Mª Alejandra Ávalos-Ramos (MDPI AG, 2024)
Universities are active agents of social change through knowledge, providing citizens with the necessary abilities to face professional challenges. This work aims to evaluate and analyse the adaptation of emotional regulation in learning situations of group work in virtual and hybrid (virtual and presential) environments, of a group of students of Physical Activity and Sport Sciences belonging to a Chilean university and a Spanish university. Method: A total of 107 students from a Chilean university and a Spanish university, all of them enrolled in the degree in Physical Activity and Sport Sciences, participated in the study. The instrument used was the Adaptative Instrument for Regulation of Emotions questionnaire. Results: The analysis of the data shows that there are some significant differences (p ≤ 0.05), between the groups of students who worked virtually and those who worked in hybrid situations, in the aspects related to personal motivations (learn from my classmates, not to disappoint my working group, and enjoying the experience of working in a group). The students who worked online resolved conflicts mainly through individual regulation mechanisms with significant differences in relation to the students who worked in hybrid mode. No significant differences were found in the socioemotional challenges or in the balance of the metacognitive experience. Conclusion: The group that worked in hybrid learning valued group purposes over personal purposes and used the social regulation mechanism over individual regulation in conflict resolution. On the other hand, the group that worked virtually valued group and personal purposes equally and used the mechanism of individual regulation and social regulation to solve difficulties. Differences between students who worked in virtual and hybrid environments may be due to greater social interaction and group dynamics in hybrid environments, as well as differences in culture and access to resources and technology.